PERANCANGAN E-CUSTOMER RELATIONSHIP MANAGEMENT PADA PT STARSINDO LOGISTICS - Nelly, Nelly; Hudiarto, Hudiarto; Yudhika, Rangga (Bina Nusantara University, 2009)
PT Starsindo Logistics is a company engaged in the field of freight forwarder. The company problem faced today is providing information to customers that are less precise and quick, especially on the customer’s order status information. This problem starts from the time of departure until time EMKL truck dock container freight customers enter the process. Therefore, it is necessary to use electronic Customer Service applications-Customer Relationship Management as it can make it easier to manage and control the flow of information about the status of customer orders. The research method is to follow the rules that exist in the Object Oriented Analysis and Design which has been introduced by Mathiassen. Through the website, the public is expected to easily access all information about the company and vessel schedules. Customers can also access information on schedule orders, tracking order status and transaction history that has been done. With the web-based Customer Service applications, it is expected to help companies build better relationships with customers.Keywords: e-customer relationship management, freight forwarding, object-oriented analysis and design